Antioxidant Potential and Phenolic Compounds of Some Widely Consumed Turkish White Bean (Phaseolus vulgaris L.) Varieties - Orak Hakime Hülya; Karamać Magdalena; Orak Adnan; Amarowicz Ryszard (Polish Journal of Food and Nutrition Sciences)
The antioxidant potential and phenolic compounds content were investigated in ten white bean varieties widely consumed in Turkey. Total phenolic contents of seeds varied between 0.33 and 0.63 mg GAE/g. The Trolox Equivalent Antioxidant Capacity (TEAC) determined by the ABTS assay and the Ferric-Reducing Antioxidant Power (FRAP) of bean varieties ranged from 3.50 to 5.17 μmol Trolox/g seed and from 7.99 to 11.20 μmol Fe2+/g seed, respectively. Strong correlations were found between total phenolic content and FRAP (r=0.850) and between TEAC and FRAP (r=0.734). The antioxidant activity was investigated in a β-carotene-linoleic acid model system, as well. Differences in the inhibition of emulsion oxidation by extracts of white bean varieties were slight. The RP-HPLC fingerprint analysis of extracts showed the presence of five dominant phenolic compounds which were described as ferulic or caffeic acids derivatives. Four of them significantly contributed to reducing power and antiradical activity against ABTS•+ of extracts.